Can Awareness Reduce (and Reverse) Identity-Driven Bias in Judgement? Evidence from International Cricket - Subhasish M Chowdhury; Sarah Jewell; Carl Singleton (Institute of Labor Economics (IZA), 2024)
Competitions often suffer from biased judgments by officials tied to their social identities. In international cricket, home nation umpires favoured home teams, but neutral umpires were introduced successfully to address this bias. However, the COVID-19 pandemic prompted the return of home umpires, creating a natural experiment amid heightened scrutiny, modern technology, and sometimes empty stadiums. Consistent with the predictions of our behavioural model, we find no evidence of in-group bias during the pandemic; instead, we observe evidence of over-compensation. The pre-pandemic home team advantage in 'leg before wicket' decisions vanished, with home umpires seemingly favouring the away opposition, compared with neutral umpires in the period before, especially in more marginal or difficult decisions. This suggests that awareness and scrutiny can not only eliminate identity-driven judgement bias but may even reverse it.
Keywords: D01; D91; L83; Z2; 330; social pressure; judgement bias; identity; natural experiment; home advantage; COVID-19